2020
DOI: 10.1002/hbm.25268
|View full text |Cite
|
Sign up to set email alerts
|

Prevent breaking bad: A proof of concept study of rebalancing the brain's rumination circuit with real‐time fMRI functional connectivity neurofeedback

Abstract: Rumination, repetitively thinking about the causes, consequences, and one's negative affect, has been considered as an important factor of depression. The intrusion of ruminative thoughts is not easily controlled, and it may be useful to visualize one's neural activity related to rumination and to use that information to facilitate one's self‐control. Real‐time fMRI neurofeedback (rtfMRI‐nf) enables one to see and regulate the fMRI signal from their own brain. This proof‐of concept study utilized connectivity‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 94 publications
3
37
1
Order By: Relevance
“…Targeting the particular FC(s) related to the particular subset(s) of symptoms that a patient displays (and not those related to subsets of symptoms that they do not display) should allow for better neurofeedback precision. A recent study by Tsuchiyagaito et al (2020) also found rumination scores to be reduced after FCNef. The targeted FC in this study was that between the temporoparietal junction and precuneus, both within DMN; it therefore shared one ROI (precuneus) with our own.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Targeting the particular FC(s) related to the particular subset(s) of symptoms that a patient displays (and not those related to subsets of symptoms that they do not display) should allow for better neurofeedback precision. A recent study by Tsuchiyagaito et al (2020) also found rumination scores to be reduced after FCNef. The targeted FC in this study was that between the temporoparietal junction and precuneus, both within DMN; it therefore shared one ROI (precuneus) with our own.…”
Section: Discussionmentioning
confidence: 76%
“…Several ‘proof of concept’ studies have already shown the potential effectiveness of real-time fMRI neurofeedback paradigms for depression (Linden et al 2012, Young et al 2014, 2017). Recently, a new type of real-time fMRI neurofeedback called functional connectivity neurofeedback (FCNef) has been developed (Koush et al 2013, Megumi et al 2015, Koush et al 2017, Ramot et al 2017, Yamada et al 2017, Yamashita et al 2017, Tsuchiyagaito et al 2020), where participants are trained to modulate functional connectivity (FC) between selected regions of interest (ROIs). This type of neurofeedback has proven effective in changing the resting-state connectivity between intrinsic brain networks in the long-term (Megumi et al 2015) and in leading to an improvement in aberrant behaviors related to neurobiological disorders (Ramot et al 2017, Yamada et al 2017, Tsuchiyagaito et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, even a less robust estimate of brain activation could be useful in training participants to self-regulate their brain state. Indeed, studies with the two-point dynamic FC neurofeedback, which is one extreme window width focusing on feedback timeliness, demonstrated successful training in self-regulating functional connectivity [30, 66].…”
Section: Discussionmentioning
confidence: 99%
“…The 16 FCs discovered in this study are promising candidates as theranostic biomarkers for depression symptoms. Future work should investigate whether modulation of FCs could be an effective treatment for depression symptoms by using an intervention method with regard to FCs, such as functional connectivity neurofeedback training (53)(54)(55)(56)(57)(58)(59).…”
Section: Discussionmentioning
confidence: 99%